Pengenalan Peralatan Musik Tradisional Melayu Riau Pada Siswa SMPN 3 Kampar Kiri Tengah Kabupaten Kampar - Amanan Amanan; Juswandi Juswandi; Hermansyah Hermansyah (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2020)
Introduction of Riau Malay Traditional Music Equipment at various levels in schools today is very lacking and so is the generation of good luck, very few people can play traditional Malay Malay music equipment at events held such as wedding receptions, traditional events held by the community.The complaint was felt by millennial generation in various educational institutions. As in students of SMP Negeri 3 Kecampar Kiri Tengah. The introduction of traditional Malay Malay musical instruments to students in various schools is still lacking, so that many in the current generation are not familiar with traditional Malay Malay musical instruments. Moreover, who can earth or play the equipment.